The new ophthalmic formulation of bilastine: current state of knowledge - Łozowski, Jan; Mordarska, Milena; Piwowarczyk, Alicja; Paluchowska, Joanna; Gołąbek, Natalia; Kodura, Alicja; Piątek, Przemysław; Białas, Julia; Szymański, Łukasz; Merc, Artur (Quality in Sport, 2026)
Background: Allergic conjunctivitis is a common ocular condition characterized by itching, redness and tearing, which significantly affect patient comfort and daily functioning. Recently, a preservative-free ophthalmic formulation designed for once-daily administration has been developed, containing the second-generation antihistamine bilastine at a concentration of 0.6%. Aim: The aim of this review was to summarize the current state of knowledge on the new ophthalmic formulation of bilastine, evaluate the available clinical evidence on its efficacy and safety and identify major research gaps and directions for future investigation. Materials and methods: A literature review was performed using PubMed, Google Scholar, ResearchGate, Embase, Scopus and Web of Science, applying the keywords: bilastine, ophthalmic, ocular, eye, conjunctivitis, eye drops, ophthalmic solution and formulation. Results: Phase II and phase III studies demonstrated a rapid onset of action and sustained symptom control for up to 16 hours following single-dose administration. Bilastine was shown to be noninferior to ketotifen in relieving ocular pruritus. An 8-week placebo-controlled study confirmed clinically meaningful improvements in patient-reported symptoms, a favorable safety profile and good tolerability. Experimental pharmacokinetic studies demonstrated high concentrations in the conjunctival tissue with minimal systemic exposure, supporting a once-daily dosing regimen. Conclusions: The 0.6% ophthalmic bilastine formulation represents an effective and well-tolerated treatment option for allergic conjunctivitis, offering the advantages of rapid onset of action, prolonged efficacy lasting up to 16 hours and a preservative-free formulation. However, scientific data remain limited regarding the safety of long-term use beyond 8 weeks, its use in pediatric populations and direct comparative studies with other commercially available ophthalmic second-generation antihistamines.